On the Levy-Baxter theorems for shot-noise fields. II - Buldygin, V. V.; Mel'nik, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish sufficient conditions under which shot-noise fields with a response function of a certain form possess the Levy-Baxter property on an increasing parametric set.